DAMPAK KAROSHI PADA KARYAWAN PERUSAHAAN DI JEPANG DEWASA INI - Kadek Febriana Theresia Kadek FebrianaTheresia; Wayan Nurita (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
Japan is a developed country that is famous for its many cultures and traditions that are still developing today. Apart from being famous for their culture and traditions, the Japanese work ethic is also very well known. They are even willing to work more than their normal working hours to show their sense of loyalty to the company where they work. Of course this has unfavorable consequences, one such phenomenon is called karoshi (過労死). This karoshi phenomenon has occurred since the 1990s in Japan. Even now, the government is still trying to overcome the karoshi that occurs in Japan. Excessive working hours and high job demands mean that karoshi still occurs frequently in Japan. This research aims to find out more deeply the reasons why employees in Japanese companies are affected by the karoshi phenomenon. Apart from that, this research also used a field research method in the form of distributing questionnaires to 15 employees of Japanese companies